2018
DOI: 10.1136/bcr-2017-223245
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial non-cirrhotic hyperammonaemic encephalopathy

Abstract: A 51-year-old female presented with acute confusion associated with a non-specific headache and lethargy. The patient's history included bipolar disorder on valproate and recent travel to northern Vietnam. The patient was subsequently found to have hyperammonaemia as well as a urinary tract infection and bacteraemia with The patient was presumed to have a multifactorial non-cirrhotic hyperammonaemic encephalopathy due to a combination of a urinary tract infection and bacteraemia with, a urease-producing bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Previous research found Klebisiella species and Pseudomonas aeruginosa can cause an increase in ammonia production. It causes non-hepatic hyperammonemia encephalopathy (16,35). They may be attributed to produce urease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research found Klebisiella species and Pseudomonas aeruginosa can cause an increase in ammonia production. It causes non-hepatic hyperammonemia encephalopathy (16,35). They may be attributed to produce urease.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few small sample size studies and case reports of NHH (15). NHH has been associated with organ failure, prolonged fasting, and urinary tract infections (16), but studies investigating the prognostic or risk factors on this topic are scarce. The objective of this retrospective cohort study was to determine what risk factors were associated with the development of NHH after hospital admission in critical care patients.…”
Section: Introductionmentioning
confidence: 99%
“…The patient presented to the same hospital and was treated predominantly by the same intensive care specialists each time. Through the patient perspective that she had written as part of the BMJ case report related to her first admission,3 we had unique insight into the issues that she had in recovering from her first critical illness. Based on this, we were able to make the informed and deliberate decision to reinstitute her usual antipsychotics and antidepressants early in her admission to hopefully alleviate some of the psychiatric issues that she had post her first critical illness.…”
Section: Discussionmentioning
confidence: 99%
“…total daily dose of 250 mg) and migraines on amitriptyline 50 mg nocte. She also had an ICU admission approximately 2 years prior, previously reported,3 for non-cirrhotic hyperammonaemic encephalopathy thought to be due to a combination of a Klebsiella pneumoniae urinary tract infection with bacteraemia and sodium valproate therapy.…”
Section: Case Presentationmentioning
confidence: 98%
“…Hyperammonemia has occured as a consequence of the reduction in the detoxification capabilities of the liver in the setting of liver failure as well as with increased intestinal production of ammonia[ 1 ]. However, several other conditions that determine an imbalance between the production and the clearance of ammonia such as infections with urease-producing bacteria, high-protein diet, malignancy, sarcopenia, renal failure, gastrointestinal (GI) bleeding, gastric bypass, and organ transplantation can also determine high ammonia levels[ 2 ] and sometimes lead to non-cirrhotic encephalopathy[ 3 ].…”
Section: Introductionmentioning
confidence: 99%